Community Empowerment through Biohack Eco-Enzyme Innovation as a Sustainable Eco-Friendly: Pemberdayaan Masyarakat melalui Inovasi Biohack Eco-Enzyme sebagai Produk Ramah Lingkungan Berkelanjutan - Djuna Lamondo; Wirnangsi D. Uno; Wiwin Kobi; Febriyanti; Rhosfiani Hasan; Kasim Ulane (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The community of Ulapato B Village possesses significant potential in developing eco-friendly products based on organic waste management, supported by the availability of raw materials. However, this potential has not been optimally utilized due to limited knowledge and technical skills. The Community Partnership Program (PKM) aims to enhance community capacity through the application of Biohack Eco-Enzyme innovation as an environmentally friendly product that can be utilized in the fields of health, agriculture, and the creative industry. The activities carried out include education, training in eco-enzyme production, hands-on mentoring, and product application. Evaluation results indicate a significant improvement across various assessed indicators, including community knowledge in waste management (85%), understanding and practical skills in eco-enzyme production (75%), utilization of eco-enzyme in health (75%), agriculture (80%), and creative industry (70%). These achievements demonstrate that the Biohack Eco-Enzyme innovation is effective in enhancing awareness, skills, and the utilization of organic waste into value-added products. This program not only contributes positively to waste reduction and environmental quality improvement but also opens opportunities for the sustainable development of a creative economy based on local resources